C16-ceramide is a natural regulatory ligand of p53 in cellular stress response. Issue 1 (December 2018) - Fekry, Baharan; Jeffries, Kristen; Esmaeilniakooshkghazi, Amin; Szulc, Zdzislaw; Knagge, Kevin; Kirchner, David; Horita, David; Krupenko, Sergey; Krupenko, Natalia
Abstract Ceramides are important participants of signal transduction, regulating fundamental cellular processes. Here we report the mechanism for activation of p53 tumor suppressor by C16 -ceramide. C16 -ceramide tightly binds within the p53 DNA-binding domain (K d 60 nM), in close vicinity to the Box V motif. This interaction is highly selective toward the ceramide acyl chain length with its C10 atom being proximal to Ser240 and Ser241. Ceramide binding stabilizes p53 and disrupts its complex with E3 ligase MDM2 leading to the p53 accumulation, nuclear translocation and activation of the downstream targets. This mechanism of p53 activation is fundamentally different from the canonical p53 regulation through protein–protein interactions or posttranslational modifications. The discovered mechanism is triggered by serum or folate deprivation implicating it in the cellular response to nutrient/metabolic stress. Our study establishes C16 -ceramide as a natural small molecule activating p53 through the direct binding. Ceramides are important participants of signal transduction, regulating fundamental cellular processes. Here authors show that C16 -ceramide binds to the tumor suppressor p53, disrupts its interaction with MDM2 and facilitates p53 accumulation and activation of its downstream targets.